Relación entre clima y compromiso organizacional en la gerencia de administración de la Municipalidad Distrital de Belén periodo 2022 - Vasquez Borges, Ursula (2023)
In this research, we sought to establish what type of relationship describes the organizational climate and organizational commitment, for this purpose a non-experimental investigation was designed, of a descriptive correlational level, of a cross-section, whose study entity was the district municipality of Belén de the province of Maynas, department of Loreto, the study population was made up of the workers of the administration management of this municipality. The research hypothesis posited that there was a direct and significant relationship between variables of human resources management; the one that was confirmed by the data obtained through the application of a survey that had as an instrument a questionnaire with a Likert-type scale; yielding the hypothesis test carried out through the Spearman coefficient a value of 0.616 with a significance of 0.004. This allowed us to conclude that there is a positive and moderately intense relationship between both variables under study.